Hepatitis E Virus: An Emerging Foodborne Pathogen - Harrison, La'Chia; DiCaprio, Erin (Frontiers in Sustainable Food Systems, 2018)
HEV is endemic in areas with poor sanitation and has traditionally been classified as a water-borne virus. Until recently, cases of HEV in industrialized countries were associated with travel to those areas. In the last decade, locally acquired cases of HEV have increased in the European Union, leading to the investigation of potential foodborne transmission of the virus. In the mid-1990’s HEV was found to be unique among other water- and foodborne viruses because of the observation of zoonotic transmission of the virus. HEV is endemic on domestic swine farms worldwide and can infect pigs of all ages. Consequently, pork liver and pork liver containing products have been identified as the source of many of the foodborne HEV outbreaks in Europe. Other pork products and game meats have also been implicated in HEV outbreaks. Finally, anecdotal evidence exists for HEV transmission via shellfish and produce. HEV disease presentation is typically a self-limiting acute hepatitis; however, chronic hepatitis and extrahepatic manifestations occur in high-risk populations. Detection and control of HEV remains challenging because an efficient cell culture system has yet to be developed. Thus, detection relies upon molecular and serological methods. No standardized method exists for the detection of HEV in foods and research on the stability of HEV in foods and the environment has been limited. This review summarizes the current knowledge available on foodborne HEV.